Violence and Non-Violence at Rock Concerts: 1970s French Society Confronted With Its Contradictions - Joann Élart (Criminocorpus)
“The hopefulness of ‘Love Power’ has gone out the window,” Michel Lancelot wrote in 1971, adding that “just about everywhere, the revolt is armed” (Campus, 1971). The author was describing the state of violence on American campuses, comparing it with the fate of public figures who championed non-violence. In France, this dichotomy spread from the usual arena of public demonstrations and found its way into pop music festivals held in the South as well as a few concerts in Paris, like the Palais des Sports, where violence erupted among rioters and ticket dodgers on January 31, 1971. On that occasion, France was in the midst of discovering pop music, and its soothing effect was said to have dissuaded the young audience from joining in the fray. The contradiction was not lost on the journalists of the time, who repeatedly noticed the apathetic, intellectual audiences who attended concerts by bands like Soft Machine. A completely different atmosphere reigned at Johnny Hallyday’s shows, which attracted a fringe group of aggressive, rebellious roughnecks and led to the implementation of considerable security measures to protect the idol. The vocabulary of violence and non-violence was systematically employed in newspaper columns to describe the wild energy emanating from performers and audience members during live performances. It was used to analyze the musical components of pop music and pub rock. Their harmonies, rhythms, intensity, loud volume, and lyrics left listeners with an impression of musical violence. The vocabulary of violence also became the norm for slogans created by advertising agencies in order to sell increasingly larger and louder amplifiers.